Optical properties and crystallization kinetics of (TeO2)(ZnO)(TiO2) glasses - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2011)
Ternary tellurite based glasses in the (TeO2)(ZnO)(TiO2) system were prepared and its optical properties and crystallization kinetics investigated by using UV-VIS spectrophotometer and differential thermal analyzer (DTA). All the glasses were transparent from visible to near infrared region for different ZnO glass compositions (x=0.05, 0.10, 0.20, and 0.30 mol). In the experiment, optical band gap and Urbach energies were estimated from the optic(a)l absorption spectra between 400 and 800 nm wavelength region. The observed results confirm that the addition of ZnO glass composition from 0.05 to 0.30 mol increases the optical band gap energy from 2.94 to 3.0 eV. In addition, glass transition (Tg), crystallization (T-p) and melting temperature (T-m) were determined by using the DTA plots. Finally, DTA results obtained with a heating rate of 20 degrees C/min show that the peak crystallization temperature increases from 463 to 533 degrees C as the ZnO content increases from 0.05 to 0.30 mol (C) 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
Keywords: energy band gap; fiber amplifier; thermal analysis; tellurite glasses